2019
DOI: 10.1002/aoc.4883
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structural studies and antimicrobial evaluation of nickel (II) complexes of NNS tridentate thiosemicarbazone based ligands

Abstract: Synthesis and characterization of three nickel complexes [NiCl(L1)] 1, [NiCl(L2)] 2 and [NiCl(L3)] 3 are described {HL1 = 4‐(2,5‐dimethoxyphenyl)‐1‐((pyridin‐2‐yl)methylene)thiosemicarbazide, HL2 = 4‐(3‐nitrophenyl)‐1‐((pyridin‐2‐yl)methylene)thiosemicarbazide and HL3 = 4‐(2,4‐dimethoxyphenyl)‐1‐((pyridin‐2‐yl)methylene)thiosemicarbazide} and among the tridentate ligands HL3 is reported for the first time. The structures of the complexes were assigned based on CHNS microanalysis, spectroscopic (IR & UV–Vis.) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…In comparison with screening of another previous synthesized Schiff base ligands by Ibrahim et al, from condensation of derivatives of pyridine‐2‐carboxaldehyde with 4‐(2,4‐dimethoxyphenyl) thiosemicarbazide and its transition metal complexes, [ 57 ] against various bacterial strains as E. coli (G − ve) and S. aureus (G + ve). The studies showed also that the free ligand had not any activity against these strains, whereas their Ni(II) complexes have higher inhibition zone diameter in the range of 13–16 mm than their corresponding ligand.…”
Section: Resultsmentioning
confidence: 99%
“…In comparison with screening of another previous synthesized Schiff base ligands by Ibrahim et al, from condensation of derivatives of pyridine‐2‐carboxaldehyde with 4‐(2,4‐dimethoxyphenyl) thiosemicarbazide and its transition metal complexes, [ 57 ] against various bacterial strains as E. coli (G − ve) and S. aureus (G + ve). The studies showed also that the free ligand had not any activity against these strains, whereas their Ni(II) complexes have higher inhibition zone diameter in the range of 13–16 mm than their corresponding ligand.…”
Section: Resultsmentioning
confidence: 99%
“…[ 98 ] In the same way we found that compound 4 has better activity (14.3 and 13.3 mm) than the Ni(II) compound [NiCl(L 1 )] (14.0 and 13.0) against S. aureus and E. coli , respectively. [ 99 ]…”
Section: Resultsmentioning
confidence: 99%
“…The ligands have shown usefulness in coordination chemistry with a chelation mode of pyridine-2-carboxaldehyde TSC ligands via the azomethine (N), pyridinyl (N), and thiolate (S) atoms in a monobasic character that has been shown by single crystal XRD studies of respective metal complexes. [7,[27][28][29][30][31] These tridentate ligands are stable at room temperature and exhibit thione-thiol tautomerism in the solid form, but the thiol conformation is predominant in the ligand solution. [28][29][30][31] The reaction of Pb (II) and Hg (II) with the TSCs took place in aqueous ethanol under refluxing conditions and the solids formed were washed extensively with boiling water to remove unreacted metal precursor.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…[7,[27][28][29][30][31] These tridentate ligands are stable at room temperature and exhibit thione-thiol tautomerism in the solid form, but the thiol conformation is predominant in the ligand solution. [28][29][30][31] The reaction of Pb (II) and Hg (II) with the TSCs took place in aqueous ethanol under refluxing conditions and the solids formed were washed extensively with boiling water to remove unreacted metal precursor. The yellow complexes were obtained in moderate yields (51%-77%) and exhibited very poor solubility at room temperature in several organic solvents, for example, methanol, ethanol, acetone, and methylene chloride.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation